Playing with religion: The gamification of jihad - Firas Mahmoud (Danish Institute for International Studies (DIIS), 2022)
This report reviews existing knowledge on the convergence between jihad and gaming, and identifies areas that need further attention from academics and practitioners concerned with the spread of transnational jihadism. As video gaming becomes ubiquitous, its growing influence also has an impact on jihadi mobilisation or other types of violent extremism. Investigating ways in which jihadists contextualise and take advantage of various gaming spaces, this report also presents examples of such conduct. The review briefly explores comparable and related fields of research, such as media and cultural studies as well as research on right-wing extremism. Presenting relevant theoretical frameworks that can be applied to the case of jihadism, the analysis points at the same time to gaps in our understanding of this incipient phenomenon for further examination and inquiry, including suggestions on practical directions for moving forward. To conclude, security measures to prevent gaming being used as platforms for mobilisation are addressed as a broad call-to-action and inspiration to multidisciplinary collaboration.
Keywords: 300; Playing with religion; jihadist gaming caces; first person shooter; digital hazards; video gaming; gaming and religion; jihadism